Effect of different shear rate on membrane performance on pes asymmetric membrane for gas separation - Nik Az Amin, Nik Abdul Aziz (2006)
Membrane based gas separation process technology has been recognized as one of the most efficient and advanced unit operation for gas separation. The main problem in membrane gas separation is the trade off between permeability and selectivity. The membrane that provide high permeability offered low selectivity and vice versa. Therefore in this study, a high performance Polyethersulfone (PES) flat sheet asymmetric membrane will be fabricated based on high of both permeability and selectivity. The main objectives of this study are to illustrate the effect of shear rate on asymmetric membrane structure and gas separation performance. The membranes are produced by a simple dry/wet phase inversion technique using a conventional method. By using several membrane with different shear rate, the membranes then been installed to the gas permeation rig and to be tested by natural gas which are oxygen and nitrogen. Then, the permeability and selectivity can be calculated. The membrane with the optimum performance was chosen for further membrane fabrication.